Morphological characteristics and motor skills of young students with different levels of engagement in physical activities (Características morfológicas y habilidades motrices de estudiantes jóvenes con diferentes niveles de participación en actividad - Batez, Maja; Krsmanović, Branko; Mikalački, Milena; Čokorilo, Nebojša; Simić, Marijana; Ruiz-Montero, Pedro Jesús (Retos, 2018)
The overall orientation of the research problem is focused on the physical activity level of the participants from the aspect of different intensities of motor engagement and their impact on morphological characteristics and motor skills with an intention of determining whether there are statistically significant differences between groups. In a sample of 103 students, aged between 18 and 20 years (18.9 ± 0.4), the female students were divided into three subsamples according to the level of physical activity: highly active, active and inactive. The study which was conducted had a transversal character. The data obtained in the survey were analysed using the univariate (ANOVA) and multivariate (MANOVA) statistical methods. The motor skills mere monitored by the use of the Eurofit Test Battery (wide-angle seated forward bend, standing long jump, pull-up endurance, 10 x 5m shuttle run and endurance shuttle run- beep test). The following morphological characteristics were considered: height, weight, body mass index, percentage of muscular mass and fat mass, as well as waist circumference. The obtained results indicate the existence of statistically significant differences between the % body muscle mass´ groups (p < 0.05) and motor skills parameters (sit and reach, p